A incorporação do conceito de sistema na Ciência da Informação: um exercício metodológico para seu entendimento - Ribeiro, Leila Beatriz (1992)
Investigation of epistemological nature on the introduction of system concept in Informations Science via academic and operational practices of information system agents in Brazil. The response to the investigation is organized on Knowledge methodologically and threoretically based aiming at the construction of the object through its course in the History of Sciences. It is structured in two levels of representation: the formal one, which gives possibility to border the object via literature dealing with system concept on classical and operational approches; the informal one, which permits to border the object on the speech of the interviewed information system agents. The match of formal x informal representation of the object is now formatted by a roll of categories constituted by elements kept in system conception and concept.